Evaluation of demand control ventilation impact on indoor air quality and energy efficiency of an office space in a tropical climate - Abadi, Chanik; Gaddafi, Ismaili; Amira Satirawaty, Mohamed Pauzan (Research Square, 2024)
Indoor air quality (IAQ) and energy efficiency are critical factors in the design and operation of office spaces. This study explores the transformative potential of Demand Control Ventilation (DCV) systems in optimizing IAQ and energy efficiency within office environments located in tropical climates. Unlike traditional ventilation mechanisms, which operate uniformly regardless of occupancy levels, thereby escalating energy expenditure, DCV systems dynamically adjust fresh air inflow based on real-time occupancy data. Through meticulous simulation analyses employing the Carrier Hourly Analysis Program (HAP), this investigation contrasts the performance of a conventional, constant ventilation setup against that of a DCV-modulated environment. This comparison utilizes actual occupancy, HVAC settings, and electrical loads. The findings reveal that DCV implementation not only upholds stringent IAQ standards but also heralds a significant reduction in average energy consumption by 38.9%. This study substantiates DCV's efficacy in enhancing IAQ and energy savings, positioning DCV as a cornerstone technology for sustainable retrofitting and design in tropical climates, and highlighting its potential applications in optimizing space ventilation systems.